Smoking Cessation as a Public Health Measure to Limit the Coronavirus Disease 2019 Pandemic - Maki Komiyama; Koji Hasegawa (European Cardiology Review)
The novel coronavirus disease 2019 (COVID-19) has already evolved into a rapidly expanding pandemic. Risk factors for COVID-19, such as cardiovascular disease, chronic obstructive pulmonary disease and diabetes, are all strongly associated with smoking habits. The effects of cigarette smoking on the transmission of the virus and worsening of COVID-19 have been less addressed. Emerging data indicate that smoking history is the major determinant of worsening COVID-19 outcomes. Smoking cessation recovers airway ciliary clearance and immune function. Thus, smoking cessation awareness is strongly encouraged as a public health measure to limit the global impact of COVID-19.